Removal of transient disturbances from oscillating measurements using nearest neighbors imputation - Ceclio,IM; Ottewill,JR; Fretheim,H; Thornhill,NF (Journal of Process Control, 2016)
Transient disturbances in process measurements compromise the accuracy of somemethods for plant-wide oscillation analysis. This paper presents a method to removesuch transients while maintaining the dynamic features of the original measurement.The method is based on a nearest neighbors imputation technique. Itreplaces the removed transient with an estimate which is based on the time seriesof the whole measurement. The method is demonstrated on experimental andindustrial case studies. The results demonstrate the efficacy of the method andrecommended parameters. Furthermore, inconsistency indices are proposed whichfacilitate the automation of the method.